Key Features of AI Applications in Foreign Language Teaching - Kır, Durmuş Barış; Tekin, Eda (Bartin University, 2025)
The purpose of this study is to assess the features of artificial intelligence (AI) applications in foreign language teaching. The study provides a framework for evaluating AI by focusing on the areas of use of AI applications and their contributions to the foreign language learning process. A qualitative research approach using document analysis was adopted as the research design and method. In this approach, it is aimed to provide guidance for developing more effective and innovative solutions in the field of language teaching by focusing on the advantages, limitations and future potential of existing AI applications. In this context, the study identified AI applications that are suitable for use in foreign language teaching, and then classified these applications under 13 categories: asking questions and getting answers, visual creation, music creation, voice-to-text conversion, audio recording, spell check, presentation preparing, video creation, voice generator, language practice, academic learning, course creation and gamification. These applications were evaluated in terms of their advantages for personalized learning, their contribution to interactive teaching methods and their status in meeting student needs. In addition, the study emphasized the importance of integrating AI into foreign language teaching activities to support learning, increase efficiency and encourage more student participation.
Keywords: Educational Technology and Computing; Eğitim Teknolojisi ve Bilgi İşlem